Implementation of Tourism Management Concept in Herbal Tourism Village as Alternative Tourism Business in the New Normal Era - Utama, I Gusti Bagus Rai; Erfiani, Ni Made Diana; Wuruwu, Dermawan; Susanto, Putu Chris; Darmawijaya, I Putu; Trimurti, Christimulia Purnama (Technium Business and Management, 2022)
The novelty of this paper is in applying the downstream innovation in the tourism concept into herbal tourism village as alternative tourism in the new normal era. This project assistance is an implementation of the results of previous research related to tourism villages, especially the Catur Tourism Village, Kintamani, Bali as a form of implementation of herbal tourism villages as alternative tourism in the new normal era towards innovation in the downstream tourism concept of the herbal tourism village. The results of this project assistance can strengthen homestay-based tourism villages in Catur Tourism Village by strengthening homestay management so that the attraction of overnight tourism increases following the standards of hospitality, cleanliness, health, safety, and environment and health procedures in the era of adaptation to new and post-pandemic habits. Lifting, creating, and selling the potential for natural, agro, herbal, and cultural tourism, through assistance in exploring, packaging, and presenting tourist attractions as something to see. Empowering and instilling the values of excellent service quality local tour guides in eco-tourism exploration as something to do. Empowering tourism village managers and villagers in developing tourism products based on the principles of Sapta Pesona, including developing and packaging Catur Village souvenir products as something to buy, so that tourists get a thorough tourism experience. Preprint posted in Research Square